Toll and Toll-like receptor signalling in development - Anthoney, Niki; Foldi, Istvan; Hidalgo, Alicia (Development (Cambridge), 2018)
The membrane receptor Toll and the related Toll-like receptors (TLRs) are best known for their universal function in innate immunity. However, Toll/TLRs were initially discovered in a developmental context, and recent studies have revealed that Toll/TLRs carry out previously unanticipated functions in development, regulating cell fate, cell number, neural circuit connectivity and synaptogenesis. Furthermore, knowledge of their molecular mechanisms of action is expanding and has highlighted that Toll/TLRs function beyond the canonical NF-κB pathway to regulate cell-to-cell communication and signalling at the synapse. Here, we provide an overview of Toll/TLR signalling and discuss how this signalling pathway regulates various aspects of development across species.